Comparison of Rhabdomyolysis in Acutely Intoxicated Patients with Psychotropic and Chemical Substances - Babulovska, Aleksandra; CHaparoska, Daniela; Velikj Stefanovska, Vesna; Simonovska, Natasha; Pereska, Zanina; Petkovska, Lidija; Kostadinoski, Kristin; Naumovski, Kiril (My University, 2023)
Introduction: Rhabdomyolysis is characterized by a muscle injury that leads to the release of intracellular muscle contents/constituents into the systemic circulation. Aim: We examined the association between the severity of the clinical presentation and creatinine phosphokinase values in patients with rhabdomyolysis acutely intoxicated with psychotropic and chemical substances. Materials and methods: This clinically controlled prospective study included 140 patients with rhabdomyolysis hospitalized at the University Clinic of Toxicology in 2019. They were divided into two groups by the substance used for intoxication (psychotropic or chemical). Results: On the third day of hospitalization, we found a significant association between the type of intoxication and the degree of rhabdomyolysis according to the poisoning severity score (p=0.0256). The significance was due to intoxications with neuroleptics – 50% (n=6), anticonvulsants – 20% (n=1), antidepressants – 16.67% (n=2), heroin – 25% (n=1), and methadone – 54% (n=6). According to the poisoning severity score, the majority of intoxicated patients with chemical substances – other gases 100% (n=1), and those intoxicated with psychotropic substances – methadone 46.67% (n=7), neuroleptics 42.67% (n=5), heroin 40% (n=2), antidepressants 8.33% (n=1), had severe rhabdomyolysis. In psychotropic intoxications, creatine kinase had a significant linear positive weak correlation with mortality (p=0.0234). Conclusions: Rhabdomyolysis and its clinical symptoms and signs were significantly more common in patients intoxicated with psychotropic substances compared to chemical intoxications. Intoxicated patients with psychotropic substances had more severe rhabdomyolysis on the third day of hospitalization. In psychotropic intoxication, with increasing creatine kinase level on the first day there was a significant increase in mortality.
Keywords: Creatine kinase; intoxication; mortality; rhabdomyolysis; poisoning severity score